2023
DOI: 10.1007/s11625-023-01294-4
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of power through transdisciplinary sustainability research: insights from a Transformative Power Lab

Abstract: If transdisciplinary sustainability research is to contribute to sustainability transitions, issues of power dynamics need to be understood and accounted for. However, examples of concrete methods that put this into practice are sparse. This paper presents a conceptual and methodological framework that develops a better understanding of the power phenomenon, while providing actionable knowledge. By focussing on the context of social innovation in energy transitions, we demonstrate how different theoretical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Multidimensional power dynamics permeate innovation patterns. The SONNET project embraced, and sought to validate and test, a multidimensional framework of power and power relations within and across social innovation initiatives 26,39 . Through the empirical case studies as well as designing and implementing a 'Transformative Power Lab', the concepts were developed and operationalized in an inter-and transdisciplinary way, resulting amongst others in seven 'ingredients' presented in a 'Power guide' aimed at supporting SIE practitioners in understanding and acting on power dynamics.…”
Section: Polandmentioning
confidence: 99%
“…Multidimensional power dynamics permeate innovation patterns. The SONNET project embraced, and sought to validate and test, a multidimensional framework of power and power relations within and across social innovation initiatives 26,39 . Through the empirical case studies as well as designing and implementing a 'Transformative Power Lab', the concepts were developed and operationalized in an inter-and transdisciplinary way, resulting amongst others in seven 'ingredients' presented in a 'Power guide' aimed at supporting SIE practitioners in understanding and acting on power dynamics.…”
Section: Polandmentioning
confidence: 99%
“…Both groups see social innovation as a bottom-up process originating from communities and from there transforming the institutional order. With their interest in “bottom-linked” and “participatory governance,” Moulaert and like-minded authors seem most interested in capacity-building aspects, whereas writers in the sustainability transitions school emphasize concrete innovations such as transition towns and energy transitions (De Geus et al , 2023; Hewitt et al , 2020; Aiken, 2017). Both groups pursue distinct, although complementary objectives focusing on democratic and inclusive governance on the one hand, and ecological sustainability on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, social innovation theorists and practitioners have borrowed existing action research strategies from these related disciplines from early on (see Weerakoon and McMurray, 2020, pp. 49/50; also De Geus et al , 2023). Community development action research strategies have most often been used to facilitate the involvement of different stakeholders for joint knowledge creation.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“… Power dynamics: Consistent with values of intergenerational equity and commitment to ‘Leave No One Behind’, TD collaborations in LMIC settings need to be cognizant of power dynamics for the proactive avoidance of potential negative impacts including inadvertent erasure of existing knowledge systems (Littman et al, 2021; Reidpath & Allotey, 2019). Mapping and making sense of power dynamics has been suggested to increase the transformative potential of TD research as suggested in natural resource management (Hakkarainen et al, 2022), in sustainability transitions (de Geus et al, 2023), in global health consortia (Pratt & Hyder, 2017), and in PAR approaches (Littman et al, 2021). As posited in collaborative governance and other fields, knowledge is emancipatory in uncovering reified power relations and unacknowledged assumptions (Innes & Booher, 2018), which are critical for shifting power dynamics (Avelino & Wittmayer, 2016).…”
Section: Towards a Practice Framework For Transdisciplinary Collabora...mentioning
confidence: 99%